Trade Policy Under Imperfect Competition: A Numerical Analysis. - Venables, A (CEPR, 1990)
This paper uses simulation techniques to investigate the effects of import tariffs and export subsidies on imperfectly competitive industries. A wide range of industries are studied and for each industry eight different types of firm and industry equilibrium concept are employed, so that the sensitivity of results with respect to equilibrium concept can be investigated. We find that results are relatively insensitive to the equilibrium concept used. Welfare gains from tariffs are robust to changes in the specification of equilibrium, although the size of these gains are small. Moving between types of equilibrium changes the magnitude of the gains from export subsidies, although only in a few cases does the sign of this effect change; the gains from export subsidies are, however, small in all case.